Role of Perceived Value and Brand Trust in Influencing the Customers’ Purchase Intention towards Mass Customized Products: A Serial Mediation Model - Thenral, E; Suganthi, Dr.L. (The journal of contemporary issues in business and government, 2020)
Customers co-create value when they participate in a mass customization process. Past studies have focused on the changing attitude of customers during the co-creation process because of their participation in the process. The unique contribution of this study is that it seeks to examine the relationships between perceived risk in opting to mass customize a product, the perceived value of mass customization, trust on the brand that mass customizes and the customers’ intention to purchase mass customized product as a serial mediation model. The results indicate that when customers perceive high value in a mass customized product, irrespective of the risk they perceive and the brand from which it is offered, their purchase intention increases towards the customized product. However, when customers want to buy a product from a trusted brand, they would buy off-the- shelf products designed and offered in an ‘as-is’ condition rather than opting to mass customize it.